A multienzyme biocatalytic cascade as a route towards the synthesis of α, ω-diamines from corresponding cycloalkanols. Issue 2 (17th November 2022) - Sarak, Sharad; Pagar, Amol D.; Khobragade, Taresh P.; Jeon, Hyunwoo; Giri, Pritam; Lim, Seonga; Patil, Mahesh D.; Kim, Yechan; Kim, Byung-Gee; Yun, Hyungdon
Abstract : We report a multienzymatic cascade for the synthesis of 1, 6-hexamethylenediamine (HMD) and related α, ω-diamines from corresponding cycloalkanols. Abstract : A multienzymatic cascade for the synthesis of 1, 6-hexamethylenediamine (HMD) and related α, ω-diamines from corresponding cycloalkanols is reported herein. In this work, an E coli -based modularization strategy was applied to distribute the complete biosynthetic pathway into different modules. The engineered transaminase variant SPTA_R417F has a beneficial impact on the cascade by driving the reaction towards target product formation. This new variant has lost >95% activity towards detrimental pyruvate, generated via auxiliary intracellular glucose metabolism in a host cell. The designed E. coli consortium including respective modules has produced 42% of HMD (from 10 mM cyclohexanol) in a one-pot-one-step manner. This developed route is the first example of a biocatalytic synthesis of HMD and related α, ω-diamines from corresponding cycloalkanols by employing E. coli -based consortia.